The Confession - Grisham, John (New York : Doubleday, 2010)
When Travis Boyette is paroled because of inoperable brain tumor, for the first time in his life, he decides to do the right thing and tell police about a crime he committed and another man is about to be executed for.
Keywords: Judicial error -- Fiction; Death row inmates -- Fiction; Legal stories; Fiction